Groin and hip quandaries - Millson, H (South African Journal of Sports Medicine, 2012)
There is little consensus on the diagnosis, pathophysiology, investigation and management of groin injuries. A key factor in making the correct diagnosis is to firstly understand the anatomy and likely generators of pain in the region. This requires an understanding of the two joints in the pelvis – the hip joint and the pubic symphysis ‒ which are at the centre of many movements. There are a multitude of varying studies on this topic. However, most importantly, many of the groin/hip pathologies can be averted by thorough and specific prehabilitation, bearing in mind the entire kinetic chain and addressing total function above and below the pelvis.